Pengaruh Kegunaan, Kepuasan Pengguna, dan Pengalaman Wisata Virtual Reality dalam Strategi Pemasaran pada Taman Bunga Celosia - Ekasari, Silvia (Jurnal EMT KITA, 2026)
This study aimed to analyze and determine the influence of usability, user satisfaction, and virtual reality tourism experience on marketing strategies at Celosia Flower Garden. The population in this study was 250 virtual reality service users for an average period of one month. To provide accurate results, the sample size was taken using the Slovin formula. Based on this calculation, the sample size for this study was 71 respondents. The research method used was SPSS. The results showed that the usability variable had a partial positive and significant effect on marketing strategies. This is evidenced by the regression coefficient value of 0.316 (positive) with a significance value of 0.007
Keywords: Usability; User Satisfaction; Virtual Reality Tourism Experience; and Marketing Strategy